The effect of digital maturity level of workplace on perceived employee well-being as moderated by locus of control - Stankevičienė , Asta; Budrionytė, Ramunė; Baniulienė, Vilma (Buhalterinės apskaitos teorija ir praktika, 2022)
Choices, determined by an employee's locus of control, affect their perceived well-being. But there is a lack of research that shows whether locus of control acts as a direct factor or a moderator. The aim of the research was to determine the effect of the level of digital maturity of the workplace on the perceived well-being of employees as moderated by the locus of control in the banking sector of Lithuania. The analysis and synthesis of scientific literature, as well as information interpretation and generalization were applied in the research. A survey of 232 employees of Lithuanian commercial banks was conducted. Descriptive statistics methods, significance tests, polynomial regression analysis were used for data analysis and formulation of conclusions. We found that locus of control moderates the relationship between employee perceived well-being and the salience of digital tools and the use of digital tools, although the relationship was weak. Employees with the dominance of internal locus of control believe that the importance of digital tools in their work is high and important, compared to the frequency of using these tools. Employees with an external locus of control tend to use digital tools more and feel greater psychological well-being when they use them to complete assigned tasks. Respondents with a high internal locus of control more often occupy high positions in the organisation, have subordinate employees and work with more complex digital tools. They are not concerned with the abundance or frequency of use of tools, but with the necessary functionality and capabilities. Therefore, the perceived psychological well-being of such employees is more influenced by the significance of digital tools.
Keywords: employee well-being; digitalization; digital maturity; digital tools; locus of control